Inspiratory Muscle Training and Functional Capacity in Patients Undergoing Cardiac Surgery - André Luiz Lisboa Cordeiro (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2016)
Introduction: Cardiac surgery is a highly complex procedure which generates worsening of lung function and decreased inspiratory muscle strength. The inspiratory muscle training becomes effective for muscle strengthening and can improve functional capacity. Objective: To investigate the effect of inspiratory muscle training on functional capacity submaximal and inspiratory muscle strength in patients undergoing cardiac surgery. Methods: This is a clinical randomized controlled trial with patients undergoing cardiac surgery at Instituto Nobre de Cardiologia. Patients were divided into two groups: control group and training. Preoperatively, were assessed the maximum inspiratory pressure and the distance covered in a 6-minute walk test. From the third postoperative day, the control group was managed according to the routine of the unit while the training group underwent daily protocol of respiratory muscle training until the day of discharge. Results: 50 patients, 27 (54%) males were included, with a mean age of 56.7±13.9 years. After the analysis, the training group had significant increase in maximum inspiratory pressure (69.5±14.9 vs. 83.1±19.1 cmH2O, P=0.0073) and 6-minute walk test (422.4±102.8 vs. 502.4±112.8 m, P=0.0031). Conclusion: We conclude that inspiratory muscle training was effective in improving functional capacity submaximal and inspiratory muscle strength in this sample of patients undergoing cardiac surgery.